ENGLISH ADVERTISING: ITS SPECIFICS AND FEATURES OF TRANSLATION INTO UKRAINIAN - Natalliia I. Talan (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
In modern science, linguistic research of advertising as a text is intensified, as advertising is an integral part of modern culture. The topicality of considering the problems associated with the translation of advertising texts is stipulated by the need to determine the degree of verbal manipulation, which is encoded in modern English and Ukrainian advertising, as well as methods and features of their rendering into Ukrainian. The purpose of the work involves consideration of English advertising and the features of its translation into Ukrainian. Research methods are method of continuous sampling, used when working with factual material, namely advertising texts, and a comparative method that revealed the common and distinctive characteristics of Ukrainian and English advertising slogans. Among the diverse number of methods, strategies, transformations and ways of translating the English advertising texts, we will highlight those that are used in the Ukrainian advertising field most often, namely: transliteration, literal (direct translation), loan translation, indirect translation, adaptation, creative translation using occasionalisms. Speaking about the methods of linguistic manipulation, we point that they include the variability and creativity of the text, as well as rhetorical figures, tropes, imagery, besides, we can mention here manipulation at different levels of language: morphological, graphic, syntactic, lexical and phonetic. The main goal is to achieve greater expressiveness and conviction. Therefore, we can conclude that advertising is a product of advertising activity, whose pragmatic orientation is the need to induce the addressee to take certain actions: purchase of goods, ordering some services. The effectiveness of an advertising campaign depends on the verbal means of influencing consumer motives. It should be noted that when translating advertising texts, the translator is to take into account a number of linguistic and cultural features: syntactic, semantic, as well as inter-contextual. What is more, the most actively perceived by the recipients is the sound image of the advertising text, because it is the key to the success of the advertising campaign, it is what attracts the attention of potential customers from the first sounds heard. After analyzing the above-mentioned methods of translating English advertising texts, we can conclude that the translator has a fairly large variety of translation transformations. For successful translation of the advertising text it is possible to allocate certain recommendations: 1) to be convinced that the advertising text should be translated. Basically, company names and some slogans are not translated into Ukrainian if they carry a minimal semantic loading; 2) to analyze the text in English, examine it for the presence of socio-cultural realities, allusions, literary parallels, metaphors, puns, polysemy; 3) to be convinced of own understanding of the maintenance of the advertising message; 4) to perform a preliminary version of the translation, choosing one of the translation methods; 5) to analyze the possible reaction of the recipients of the translated text, taking into account the cultural and age characteristics of the target audience, if necessary, make changes to the translated text; 6) to make a translation decision, perform the final version of the translation based on the fact that as accurately as possible to convey the content, emotional message and spirit of the advertising text of the original language.